1985
DOI: 10.1093/oxfordjournals.aje.a114199
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Factors and the Incidence of Cancer of the Stomach

Abstract: A case-control study of diet and stomach cancer was conducted during 1979-1982 in Toronto, Winnipeg, and St. John's Canada. Two hundred forty-six histologically verified cancer cases were individually matched by age, sex, and area of residence to 246 randomly selected population controls. Daily nutrient consumption values were calculated from quantitative diet history questionnaire data through use of the US Department of Agriculture Food Composition Data Bank, which was extended and modified for Canadian item… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

15
122
6
3

Year Published

1990
1990
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 274 publications
(146 citation statements)
references
References 0 publications
15
122
6
3
Order By: Relevance
“…Duration of refrigerator use or freezer use was not associated with stomach cancer risk in the Netherlands Cohort Study, in contrast with the results of casecontrol studies performed in Europe or the USA, which rather consistently reported a decreased stomach cancer risk with long-term use of a refrigerator [2,5,9,16,18,38,54]. Three of the case-control studies did not find an association [15,44,47] and no other cohort study reported on this association.…”
Section: Discussionmentioning
confidence: 65%
“…Duration of refrigerator use or freezer use was not associated with stomach cancer risk in the Netherlands Cohort Study, in contrast with the results of casecontrol studies performed in Europe or the USA, which rather consistently reported a decreased stomach cancer risk with long-term use of a refrigerator [2,5,9,16,18,38,54]. Three of the case-control studies did not find an association [15,44,47] and no other cohort study reported on this association.…”
Section: Discussionmentioning
confidence: 65%
“…A link between stomach cancer and poor food storage is supported by two case-control studies (Coggon et al, 1989;Risch et al, 1985) and, if real, might explain part of the world-wide decline in the disease over recent decades. In our analysis, however, stomach cancer correlated less strongly with the proportion of families living in small houses than with the proportion in overcrowded dwellings (Table III).…”
Section: Discussionmentioning
confidence: 96%
“…In most studies a statistically significant inverse association was reported between nitrate intake from foods and gastric cancer risk (Risch et al, 1985;Buiatti et al, 1990;Boeing et al, 1991;Gonzalez et al, 1994;Hansson et al, 1994;La Vecchia et al, 1994), which disappeared after additional adjustment for potential confounders (mainly intake of vitamin C and beta-carotene). In all case-control studies on nitrate and gastric cancer risk, a positive association was reported (Risch et al, 1985;Buiatti et al, 1990;Gonzalez et al, 1994;Hansson et al, 1994;La Vecchia et al, 1994;Pobel et al, 1995) which reduced after adjustment for intake of other nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…Case-control studies have mainly investigated the association between nitrate or nitrite from foods and gastric cancer risk (Risch et al, 1985;Buiatti et al, 1990;Boeing et al, 1991;Palli et al, 1992;Gonzalez et al, 1994;Hansson et al, 1994;La Vecchia et al, 1994;Pobel et al, 1995). In most studies a statistically significant inverse association was reported between nitrate intake from foods and gastric cancer risk (Risch et al, 1985;Buiatti et al, 1990;Boeing et al, 1991;Gonzalez et al, 1994;Hansson et al, 1994;La Vecchia et al, 1994), which disappeared after additional adjustment for potential confounders (mainly intake of vitamin C and beta-carotene).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation